Proceedings of the 14th International Symposium on Systems Synthesis - ISSS '01 2001
DOI: 10.1145/500001.500006
|View full text |Cite
|
Sign up to set email alerts
|

An optimal memory allocation for application-specific multiprocessor system-on-chip

Abstract: We present a novel and systematic approach for the design of shared memory architectures in the case of application-specific multiprocessor system-on-chip. This paper focuses on a memory allocation step which is based on an integer linear programming model. It permits one to obtain an optimal distributed shared memory architecture minimizing the global cost to access the shared data in the application, and the memory cost. Our approach allows automatic generation of an architecture-level specification of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Data parallelism to improve performance in a system of homogeneous multiprocessor systems is mainly the main focus of many of such research. In order to obtain optimal distributed shared memory architecture to reduce the memory and data access costs, Meftali et al [13] used an optimal integer linear programming formulation. Kandemir et al [14] used a compiler based approach to optimize energy and memory access latency on MPSoCs.…”
Section: Related Workmentioning
confidence: 99%
“…Data parallelism to improve performance in a system of homogeneous multiprocessor systems is mainly the main focus of many of such research. In order to obtain optimal distributed shared memory architecture to reduce the memory and data access costs, Meftali et al [13] used an optimal integer linear programming formulation. Kandemir et al [14] used a compiler based approach to optimize energy and memory access latency on MPSoCs.…”
Section: Related Workmentioning
confidence: 99%
“…Meeuwen et al presented a technique for cost-efficient interconnect architecture exploration by time-multiplexing the data transfers over a number of shared buses assuming distributed memory systems under predetermined memory allocation [8]. Meftali et al found performance-optimal shared memory allocation considering area of communication channel and memory subsystem using integer linear programming (ILP) in a point-to-point communication architecture [9]. Lahiri et al proposed an exploration technique optimizing the component mapping to bus and the bus protocol such as DMA block transfer size and bus priority assignment for a given bus topology [5].…”
Section: Related Work and Our Contributionmentioning
confidence: 99%
“…Unfortunately, only limited research exists in reducing the energy cost of the memory system. [10] and [31] describe both a heuristic which does allocation, assignment, scheduling of multiple task-graphs. [24] and [58] compile a task-graph on a given heterogeneous architecture.…”
Section: Memory Optimization In Multi-threaded Applicationsmentioning
confidence: 99%